Basic K'ichee' grammar: 38 lessons - Mondloch, James L., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
A pedagogical rather than reference grammar, the book is a thorough presentation of the basics of the K'ichee'-Maya language organized around graded grammatical lessons accompanied by drills and exercises. K'ichee'an languages occupy a prominent place among indigenous languages of the Americas, both in speakers and historical significance.--Provided by publisher.
Revised edition.
Text in English and Quiché.
Keywords: Quiché language -- Grammar